Basic income and a public job offer: Complementary policies to reduce poverty and unemployment - Felix FitzRoy; Jim Jin (Institute of Labor Economics (IZA), 2017)
Unconditional basic income, or a job guarantee by government as employer-of-last-resort, are usually discussed as alternative policies, though the first does not provide the benefits of an earned income and a good job to the growing numbers in precarious- or under-employment, while the second fails to assist those who would prefer to remain in self-employment or particular occupations if their incomes were higher, rather than to work under a JG. Furthermore a JG cannot support those who are unwilling to work. We argue here that the only cost-effective policy for comprehensive welfare is a combination of a modest basic income with job offer by local authorities below the minimum wage.
Keywords: H53; 330; basic income; job guarantee; poverty; unemployment